Power in words: An Analysis of the Flaming Devices in President Vladimir Putin's Speech Before the February, 2022 Attack on Ukraine - Ugoala, Bibian (NIU Journal of Humanities; Vol 7 No 2 (2022): NIU Journal of Humanities, Vol. 7 No. 2, June 2022, 2022)
The importance language plays in interpersonal and in intergroup relations can never be over-emphasised. Language can be used to make things happen, and also to prevent things from happening. The aim of this study is to demonstrate that how language is used determines the outcomes of its usage in intergroup and interpersonal relations. Hinging on the affordance language has, this study examines flaming devices in ten excerpts purposively chosen from the speech of President Vladimir Putin, the President of Russia in his bid to explain the reason for the decision to wage war in Ukraine. The study adopts the analytical tools of Critical Discourse Analysis espoused in van Dijk (1998). The objectives of the study are: to identify the flaming items in President Putin's speech; and to point out the potential danger President Putin advertently and inadvertently sends across through the identified flaming devices. The findings reveal that Putins used derogatory words, phrases and clause when referring to Ukraine, US, and Nato in his speech; these have flaming tendencies; the reference to Ukraine, US, and Nato at some point in the speech are overt, and covert. The flaming devices have the tendency to infuriate the target(s) of the speech, and elicit negative reactions. The study recommends that since the world has become a global village, discourses of prominent persons should be devoid of devices that have the propensity to infuriate the hearers and stimulate negative feelings and reactions. Keywords: Flaming words, Us and them, derogatory words, Russia/Ukraine war.